PENDAMPINGAN KEPADA MASYARAKAT DESA SUKAJADI KECAMATAN CARITA DALAM PENJUALAN KERUPUK IKAN PINDANG DI MARKETPLACE SHOPEE - Wahyiah, Ita Rosita; Endayani, Endayani; Fatoni, Malik; Widodo, Wahyu; Rendiyani, M; Waris.P, Achmad Nur; Marhamah, Aliatun; Nisa, Aulia; Sefriyandi, Andi; Pratama, Ahmad Yudha Eka (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
KKM UNIBA Group 63 conducted a mentoring program for the community of Sukajadi Village, Carita District, in selling pindang fish crackers on the Shopee marketplace to improve digital skills, expand market reach, and increase community income through online marketing. Sukajadi Village is famous for the production of quality pindang fish crackers, but the sales of these products are still limited to the local market due to lack of access and knowledge about digital marketing. The assistance was carried out through several stages, namely training on the use of the Shopee platform, creating a seller account, developing a digital marketing strategy, and optimizing product listings. The results of this mentoring showed a significant increase in the community's knowledge and skills regarding online sales. The community is able to create and manage an online store on Shopee, utilize the available features to increase product visibility, and organize effective promotional strategies. Sales of pindang fish crackers through Shopee increased significantly, as evidenced by the increase in the number of orders and revenue. In addition, the program also has a positive impact on the economic empowerment of the village community, with more community members involved in the production process and product sales.